Role of nuclear energy in Singapore : public acceptance, perceptions, and strategic policymaking - Lim, Nicholson Si Hao (2018)
This paper investigates the public acceptance of nuclear power generation among Singapore residents across sociodemographics to identify the key variables of significant influence that perpetuate varying intensities of positive and negative acceptance, so that a public communication strategy can be established to address misconceptions of nuclear power operation. The outcomes also serve as a validation study of the prevalent determining variables. A secondary research objective is to examine the variables that determine the public’s trust orientation towards local mainstream media with respect to the communication of nuclear power developments and in the crisis context. Given the media’s responsibility as a primary tool of public communication and its tainted track records in the Fukushima nuclear incident, this study will determine if the degree of trust in authorities qualifies as a mitigating factor by considering the interactions between the state and local media.